The Effectiveness of PjBL-STEAM Using GeoAI Media: Junior High School Students' Creative Thinking Skills - Ajeng, Ajeng; Rinto, Rinto; Fatnah, Nurwanti (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
The problem identified in this study stemmed from the condition of science learning, which remained limited to the learning model and media used, resulting in less effectiveness in developing creativity. Therefore, this study was conducted to test the effectiveness of the Project Based Learning (PjBL) model integrated with the Science, Technology, Engineering, Arts, and Mathematics (STEAM) approach using Geospatial Information System Artificial Intelligence (GeoAI) media in improving students' creative thinking skills. This study used a mixed-methods design with an embedded experimental model, where the data collection techniques were carried out through pre-research interviews, pretests and posttests, questionnaires, and interviews after the intervention. The research sample consisted of second-semester students from class VIII at Public Junior High School 1 Weru. We processed the data using normality tests, homogeneity tests, paired sample t-tests, independent sample t-tests, and N-Gain tests. The results showed a significant increase in creative thinking skills in the experimental class. The improvement was evidenced by the results of the average pretest score of 66.32, then the posttest increased to 90.44, with a very significant difference compared to the control class. The N-Gain test also recorded improvements, with an average score of 0.69 in the moderate category. This finding is reinforced by qualitative data from questionnaires and interviews, which showed a very positive response from students to the GeoAI-assisted PjBL-STEAM model, achieving an average score of 75.99% out of a maximum score of 100%.